Assessment of the humification degree of peat soil under sago (Metroxylon sagu) cultivation based on Fourier Transform Infrared (FTIR) and Ultraviolet-Visible (UV-Vis) spectroscopic characteristics - Sim Siong, Fong; Mohd Effendi, Bin Wasli; Yong, C. M. R.; Howell, P. S.; Cecelyea, Jumin; Safie, N. A.; Samling, Benedict (International Mire Conservation Group and International Peatland Society, 2017)
Sago palm (Metroxylon sagu) is a tropical crop that can survive the acidic conditions of peat soil, which is cultivated at large scale in Sarawak (Malaysia). The performance of sago palm on deep peat is variable, and not all specimens are able to grow to maturity and produce a trunk. It is hypothesised that sago growth may be influenced by peat humification because a positive relationship between the fertility of peat soil and its degree of humification has been well reported. This article investigates the humification degree of peat soil used for cultivation of sago palms, as indicated by spectroscopic characteristics. The peat soil adjacent to trunking and non-trunking palms was sampled and compared with exposed uncultivated peat. The results showed that, where largely undecomposed woody material predominated in the underlying peat, degree of humification decreased with increasing depth. Uncultivated peat was more highly humified than cultivated peat because the latter was continuously replenished with new plant matter. On the basis of FTIR spectroscopy, no significant difference was found between cultivated peat sampled adjacent to trunking and non-trunking palms. On the other hand, the UV-Vis and FTIR data suggested lower humification degree in the underlying peat which may have led to inconsistent growth.